Training for Future Esp Trainers: Evaluating the Training of Trainers (TOT) Program in Labuan Bajo, Manggarai Barat, Flores - Irfan Rifai (Bina Nusantara University, 2013)
By cooperating with Yayasan Komodo Kita and Mandiri Bank, English department of Binus University was chiefly in charge of a 15 day Training Of Trainers (TOT) program for 24 participants prepared for teaching English in Labuan Bajo, Flores. The training was aimed to prepare already fluent- in – English- teachers, tour guides, and university graduates with the right tools and method in teaching English. To assess the program, a set of evaluation questionnaire was given to the participants to know their responses on the training material, the trainers, and the program by using Likert’s scale type questions. An observational record was also used as a tool to measure participants’ achievement. The questionnaire reveals that the participants respond positively to the program and the material and favor the approaches made by the trainers during the training. However, the training shows various results in participants’ performance. It is assumed that the non teaching background of the majority of participants and the level of English as two key factors influencing their performance.